Fat droplets in the cerebrospinal fluid (CSF) spaces of the brain - Mark Reed; Christopher Miller; Cortney Connor; Jason S. Chang; Forshing Lui (AIMS Neuroscience)
It is rare to find free floating fat droplets in the cerebral spinal fluid (CSF) spaces of the brain. When fat droplets are seen in the CSF spaces, the most common cause is the rupture of a dermoid cyst. Dermoid cysts are congenital inclusion cysts that form during the neural tube closure between the third and fifth weeks of embryogenesis. In this case report, we describe a case of a 74-year-old, right-handed female who presented with an acute onset of visual disturbances and left-hand numbness. Computed tomography (CT) and magnetic resonance imaging (MRI) of the head revealed hypodense “lesions” in the lateral ventricles and basal cisterns. The CT Hounsfield unit was between −41 to −83 Hounsfield Units, which is compatible with fat rather than air. The T1 weighted and FLAIR MRI showed hyperintense lesions “floating” on top of the CSF in the lateral ventricles, which is typical for fat droplets, presumably caused by a ruptured dermoid cyst. This case emphasizes the importance of analyzing Hounsfield Units to distinguish lesions by density, where fat ranges from −50 to −150 Hounsfield Units and air is −1000 Hounsfield Units. Pneumocephalus is the presence of air in the epidural, subdural, or subarachnoid space and can cause confusion, nausea, seizures and focal neurological symptoms. A careful analysis of the neuroimaging findings in the CT with or without MRI is important in making a correct diagnosis of a ruptured dermoid cyst versus pneumocephalus.